An overview of ethnography in healthcare and medical education research - Goodson, Leigh (National Health Personnel Licensing Examination Board of the Republic of Korea, 2011)
Research in healthcare settings and medical education has relied heavily on quantitative methods. However, there are research questions within these academic domains that may be more adequately addressed by qualitative inquiry. While there are many qualitative approaches, ethnography is one method that allows the researcher to take advantage of relative immersion in order to obtain thick description. The purpose of this article is to introduce ethnography, to describe how ethnographic methods may be utilized, to provide an overview of ethnography's use in healthcare and medical education, and to summarize some key limitations with the method.